Photokeratoconjunctivitis Symptoms among Informal Welding Operators in North Samarinda, Indonesia - Iwan Muhamad Ramdan; Siti Badriatul Mursyidah; Siti Jubaedah (Global Medical & Health Communication (GMHC), 2017)
Informal sector has been contributing to the national economy but occupational health and safety practices in the sector has not been satisfactory. One of the informal sector which are found in North Samarinda is informal welding workshop, with dominant hazards is exposure to ultraviolet rays that can cause photokeratoconjunctivitis. The Objective of this study was to investigate the symptoms of photokeratoconjunctivitis and related factors among informal welding operator in North Samarinda. A cross-sectional study was conducted on 40 respondents. Research was conducted in March until November 2016. Data collection using ultraviolet detector meter, clamps meter, and questionnaire. Data analysis using chi-square, Pearson’s correlation product moment and multiple linear regression. 50% of respondents have photokeratoconjunctivitis symptoms. Personal protective equipment (PPE) (p=0.004), UV exposure duration (0.056), knowledge of health and safety (p=0.055) and number of working days (p=0.001) were associated with photokeratoconjunctivitis symptoms. Work location (p=0.244), level of education (p=0.680), age (0.167), intensity of UV radiation (p=0.206) and strength of welding current (p=0.085) were not related to photokeratoconjunctivitis symptoms. In conclusions, photokeratoconjunctivitis symptoms is influenced by the use of PPE, UV exposure duration, knowledge of health and safety, and number of working days. The most influential factor to the appearance of photokeratoconjunctivitis (β=0.32) is duration of UV exposure.GEJALA PHOTOKERATOCONJUCTIVITIS PADA PEKERJA LAS INFORMAL DI SAMARINDA UTARA, INDONESIASektor informal telah berkontribusi terhadap perekonomian nasional, namun praktik kesehatan dan keselamatan kerja pada sektor ini masih belum memuaskan. Salah satu usaha sektor informal yang banyak dijumpai di Samarinda Utara adalah usaha pengelasan dengan potensi bahaya utama paparan sinar ultraviolet yang dapat menyebabkan photokeratoconjunctivitis. Penelitian ini bertujuan menginvestigasi kejadian photokeratoconjunctivitis dan faktor yang memengaruhinya pada operator las informal di Kelurahan Samarinda Utara. Penelitian cross-sectional telah dilakukan terhadap 40 responden pada bulan Maret sampai November 2016. Pengumpulan data menggunakan UV detector meter, clamp meter, dan kuesioner. Analisis data menggunakan chi-square, Pearson’s correlation product moment, dan multiple linear regression. Lima puluh persen responden mengalami gejala photokeratoconjunctivitis. Alat pelindung diri (APD) (p=0,004), durasi paparan UV (0,056), pengetahuan tentang kesehatan, dan keselamatan kerja (K3) (p=0,055) dan jumlah hari kerja (p=0,001) berhubungan signifikan dengan kejadian photokeratoconjunctivitis. Lokasi kerja (p=0,244), tingkat pendidikan (p=0,680), usia (0,167), intensitas radiasi UV (p=0,206), dan kuat arus las (p=0,085) tidak berhubungan dengan gejala photokeratoconjunctivitis. Simpulan, gejala photokeratoconjunctivitis dipengaruhi oleh penggunaan APD, durasi paparan UV, pengetahuan K3, dan jumlah hari kerja. Faktor yang paling dominan memengaruhi gejala photokeratoconjunctivitis adalah durasi paparan UV.